2013
DOI: 10.1016/j.chiabu.2013.04.017
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of trauma focused cognitive behavioral therapy for children in Zambia

Abstract: Objectives To monitor and evaluate the feasibility of implementing Trauma Focused-Cognitive Behavioral Therapy (TF-CBT) to address trauma and stress-related symptoms in orphans and vulnerable children (OVC) in Zambia as part of ongoing programming within a non-governmental organization (NGO). Methods As part of ongoing programming, voluntary care-workers administered locally validated assessments to identify children who met criteria for moderate to severe trauma symptomatology. Local lay counselors implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
124
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 58 publications
(74 reference statements)
2
124
0
Order By: Relevance
“…Given the inconsistent results across settings, however, it may be better to start with World Health Organization recommendations for treatment of PTSD in children and adolescents. A remaining key research question here is how existing evidence-based interventions, often tested in more highly resourced research settings, can be effectively disseminated and implemented in real-world health-care settings [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Given the inconsistent results across settings, however, it may be better to start with World Health Organization recommendations for treatment of PTSD in children and adolescents. A remaining key research question here is how existing evidence-based interventions, often tested in more highly resourced research settings, can be effectively disseminated and implemented in real-world health-care settings [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…10 We have conducted studies in Zambia to understand local mental and behavioral health problems, validate mental and behavioral assessment instruments, and examine the cross-cultural feasibility of evidence-based treatment. [11][12][13][14][15] These studies culminated in the randomized clinical trial reported in this article, which tests the effectiveness of trauma-focused cognitive behavioral therapy (TF-CBT; http://tfcbt.musc.edu/) 16 for OVC compared with treatment as usual (TAU) provided by lay counselors without previous mental health care training. This trial was a collaboration with Serenity Harm Reduction Programme Zambia, a local nongovernmental organization.…”
mentioning
confidence: 99%
“…It is also important to note that the dropout rate was high (39.5%) and that post-treatment data were estimated for more than a third of the sample. Finally, several other TF-CBT effectiveness trials have been completed, with preliminary findings presented but not yet published: preliminary findings with children in foster care (Dorsey, Cox, Conover, & Berliner, 2010; Lyons, Weiner, & Scheider, 2006) and several cross-cultural studies (Cinamon, Zorzella, Thornback, Konanur, & Muller, 2011; Dorsey, Murray, Balusubramanian, & Skavenski, 2011; Murray et al, manuscript submitted). …”
mentioning
confidence: 99%